The Role of the Ministry of the Interior of the Republic of Serbia in the Conduct of Ethnic Cleansing of the Albanian Population in Kosovo and Metohija From 1998 to 1999 (Kriminalističke teme, 2022)
The paper presents a short chronology of the political conflict in the Autonomous Province of Kosovo and Metohija (Socialist Autonomous Province of Kosovo, until the constitutional changes of 1989), which in the 1990s turned into an armed conflict in which the security forces of the Republic of Serbia from October 1998 to June 1999, carried out a planned action of ethnic cleansing of Kosovo Albanians. In the action, several thousand Albanian civilians were executed extrajudicially and between 800,000 and 850,000 Albanians were forcefully expelled to Macedonia, Montenegro, Albania and Bosnia and Herzegovina. This paper is based on the final judgments of the International Criminal Tribunal for the former Yugoslavia (ICTY) by which the highest state officials and military and police generals in the Federal Republic of Yugoslavia and the Republic of Serbia were convicted of joint criminal enterprise aimed at altering the ethnic structure in at least 13 Kosovo municipalities, especially in the period of the NATO alliance campaign from March 24 to June 12, 1999. The role of the Ministry of Interior in the joint criminal enterprise (JCE), as established by the ICTY judgments to the then Ministry of Interior leaders: Vlastimir Đordđević, head of the Public Security Department, Sreten Lukić, head of the Ministry of Interior Staff for Kosovo, (Vlajko Stojiljković, the Minister of Interior, was also accused, but he committed suicide in 2002) - is undoubted. Therefore, it calls for a public analysis and presentation of the role of this part of the repressive apparatus of the state of Serbia in the ethnic cleansing of Kosovo Albanians, as well as its role in the planned and systematic concealment of crimes. The concealment of the crime was conducted from March to June 1999 by the Ministry of Interior forces through secret operations of transfer of bodies of Kosovo Albanians from primary graves in Kosovo and their burial in mass graves at secret locations in Serbia. Three graves were discovered in 2001 and one in 2013, with the assumption that there are more because they are looking for another 1,086 Albanian victims and 562 victims of Serbs, Roma, Bosniaks, Egyptians, Ashkali and others.